(untitled) (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2024)
These bud leaves have been used in traditional medicine for a variety of health conditions. However, research on the potential SPF of Benincasa hispida has not been found This study aims to conduct phytochemical screening tests and determine the Sun Protection Factor (SPF) value of kundur leaves (Benincasa hispida). The research methods used include extraction and determination of SPF values from Benincasa hispida extract at wavelengths of 290-320 nm using a UV-Vis spectrophotometer. he research results show that a concentration of 1000 ppm produces an SPF value of 25.89. And positive phytochemicals contain compounds such as flavonoids, terpenoids and saponins. The resulting SPF value shows that Benincasa hispida extract has the potential as a natural sun protection ingredient in the Ultra Protection category